Effect of nitrogen level and leaf cutting frequency on foliage and seed yields of coriander - Moniruzzaman, M; Rahman, MM (Bangladesh Journal of Agricultural Research, 2015)
A field experiment was conducted at BSMRAU farm, Gazipur to evaluate the effects of four nitrogen levels (0, 40, 80 and 120 kg/ha) and four levels of leaf cutting ( no cutting, one cutting at 30 DAS), two cuttings at 30 & 45 DAS and three cuttings at 30, 45 & 60 DAS ) on three genotypes of coriander (Coriandrum sativum L.) (CS001, CS002 and CS003). The genotype CS003 produced the highest foliage yield (8.92 t/ha) and the genotype CS001 gave the highest seed yield (0.93 t/ha). The maximum foliage and seed yields were obtained from the N application at 80 kg N/ha. The maximum foliage yield (11.21 t/ha) was recorded with the three cuttings, but the highest seed yield was noted with the one cutting (1.06 t/ha). The 80 kg N/ha coupled with three cuttings gave the top most foliage yield while the same rate accompanied with one cutting gave the top most seed yield for all genotypes. Bangladesh J. Agril. Res. 40(1): 53-60, March 2015